Chipko movement: of floated myths and flouted realities - Bandyopadhyay, Jayanta (1999)
On the 25th anniversary of the Chipko movement, this is a tribute to the courageous activists and men and women of determination who brought Chipko from a possible instrument of struggle to a trend-setting achievement. Also an examination of media created `messages' to dispel some of the myths about the movement, in particular, the question was Chipko about economics or deep ecology and was it feminist. - Reproduced
Keywords: Chipko movement; Forests